ANALISIS PROBLEMATIKA TANTANGAN MADRASAH SEBAGAI TIPOLOGI LEMBAGA PENDIDIKAN ISLAM DAN SOLUSI DALAM MENGHADAPI ERA GLOBALISASI - Mudlori, Moh Imron; Basit, Abdul (STAI Ma'had Aly Al-Hikam Malang, 2019)
At this time, the madrasah as the typology of Islamic education faces various challenges such as the difficulties of learners in understanding the subjects, the educator is also a problem if it does not meet the criteria as an educator so that the lesson can not be understood by the students as well as the management as a problem in learning if can not organize all that is needed in learning either in the form of device, curriculum and so on, also means to be inhibiting in learning so that denagan means adequate infrastructure then learning will run denagn baiak, environmental problem, environment is place of intraction learners so that when environment does not support it will be an obstacle in learning Islamic education, thus requiring some solutions to solve the problems faced by madrasah. Therefore, the author tries to provide solutions that can provide a way out so that the madrasah as a typology of Islamic education can maintain its religious values and can compete with other institutions that have advanced, because at this time with the development of science technology so that an institution in demand for compete in the success of an educational institution.